Bentuk Dan Strategi Kesantunan Direktif Menasihati Siswa Dalam Bimbingan Konseling Di Smp Muhammadiyah Program Khusus Surakarta Dan Implementasinya Sebagai Bahan Ajar Bahasa Indonesia - Windiyanti, Yuli, Prof. Dr. Harun Joko Prayitno, M.Hum, Prof. Dr. Abdul Ngalim, M.Hum (2016)
The purpose of this study was to describe: Forms and Politeness Strategy Directives Advising Students in Counseling, and its implementation as learning the Indonesian language teaching materials. Research was conducted on speech teachers and pupils in learning counseling. The method used in this research is descriptive qualitative methods, as well as using fixed strategy (embedded research). Data collection techniques in this study using techniques see, record, and record. There are three things as a result of research on the form and strategies of politeness directive advising students in counseling consisting of 58 data. 1) The form of politeness TTD advising students in the counseling containing eight subfokus form of politeness directive 1). Bermodus imperatives include the Sub-KD ruled as much as 3 or 8%, 2). Berformatif explicitly includes the Sub-KD prohibit as much as 2 or 5%, and ask for as much as 1 or 2%, 3). Berformatif fenced includes Sub-KD reprimanded by 1 or 2%, 4). The revelation of desire include Sub-KD suggest as many as 1 or 2%, 5). The revelation of the question includes the Sub-KD reprimanded by 1 or 2%, and reminds many as 1 or 2%, 6). Berpernyataan advice covering Sub-KD suggest as many as 4 or 10%, 7). Strong gestured includes Sub-KD reprimand sebanyak2 or 5%, and requires as much as 1 or 2%, and 8). Smooth gestured includes Sub-KD expect as much as 1 or 2%, to direct as much as 1 or 2%, and reminds many as 1 or 2%. 2) Strategies and techniques politeness directive advising students in counseling containing strategies and techniques: direct strategy. 3) These findings can be implemented as a pragmatic course teaching materials FKIP PBSI UMS.